Sensitivity to scale of willingness-to-pay within the context of menorrhagia - Sanghera, Sabina; Frew, Emma; Gupta, Janesh Kumar; Kai, Joe; Roberts, Tracy Elizabeth (Wiley, 2017)
Objectives: Willingness-to-pay (WTP) provides a broad assessment of well-being, capturing benefits beyond health. However, the validity of the approach has been questioned and the evidence relating to the sensitivity of WTP to changes in health status is mixed. Using menorrhagia (heavy menstrual bleeding) as a case study, this exploratory study assesses the sensitivity to scale of WTP to change in health status as measured by a condition-specific measure, MMAS, which includes both health and non-health benefits. The relationship between EQ-5D and change in health status is also assessed.